Effect of Managerial Ownership and Gender Diversity on Directors on Tax Avoidance with Audit Quality as a Moderation Variable - Harahap, Ruth Bae Eliani; Masripah, Masripah (BIMA Journal (Business, Management, & Accounting Journal), 2023)
This research was conducted to ascertain and analyze the effect of managerial ownership and gender diversity on directors on tax avoidance with audit quality as moderation. This study also adds two control variables, namely profitability and firm size. The samples in this study used mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period and were sorted using the purposive sampling method so that 75 samples were obtained. By using multiple linear regression tests, the results of managerial ownership and gender diversity in directors have no effect on tax avoidance. Then audit quality strengthens the effect of managerial ownership on tax avoidance, and audit quality weakens the effect of gender diversity on directors on tax avoidance.